2011
DOI: 10.1002/chir.21025
|View full text |Cite
|
Sign up to set email alerts
|

HPLC–CD selectivity assay for alcohol dehydrogenases

Abstract: Enantioselective reductions are a key to successful target-oriented syntheses. Finding the most suitable conditions is often a tedious work that is especially hampered by the time-consuming analytical investigation. A possible solution is the combined use of high-performance liquid chromatography and circular dichroism to find a suitable system for providing enantiomerically pure alcohols. This investigation led to an efficient protocol for the alcohol dehydrogenase-catalyzed reduction of 1-phenyl-2-propyn-3-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The ee of the phenyl ester was determined using the same conditions as the methyl ester [ t R ( S ) = 16.32 min, t R ( R ) = 18.07 min]. Because the enantiomers of the p NP ester could not be separated by chiral HPLC, the ee was determined by measuring the g factor (dissymmetry factor) with achiral HPLC with CD detector [54][56]. Column: Hyperclone ODS C18, conditions: 90∶10, CH 3 CN:H 2 O, 0.5 ml/min, 220 nm, t R (ibuprofen) = 2.7 min, t R ( p NP ester) = 4.5 min.…”
Section: Methodsmentioning
confidence: 99%
“…The ee of the phenyl ester was determined using the same conditions as the methyl ester [ t R ( S ) = 16.32 min, t R ( R ) = 18.07 min]. Because the enantiomers of the p NP ester could not be separated by chiral HPLC, the ee was determined by measuring the g factor (dissymmetry factor) with achiral HPLC with CD detector [54][56]. Column: Hyperclone ODS C18, conditions: 90∶10, CH 3 CN:H 2 O, 0.5 ml/min, 220 nm, t R (ibuprofen) = 2.7 min, t R ( p NP ester) = 4.5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Introduction of a trimethylsilyl (TMS) group, which can be attached and also removed easily, to the alkyne unit was sufficient to produce enantiopure ( R )‐3‐butin‐2‐ol ( ee >99 % compared to 60 % ee without TMS) . In our previous studies we additionally observed that compared to the desilylated compound the ADH‐catalyzed reduction of phenyl‐3‐(trimethylsilyl)‐2‐propynone provides the desired enantiopure alcohol in a more reasonable time. Because the synthesis of the TMS‐attached acetylene 16 is also more straightforward, it was performed starting from methyl 2‐bromoacetate ( 17 ) and 3‐(trifluoromethyl)‐phenol ( 15 ) as available starting materials (Scheme ).…”
Section: Figurementioning
confidence: 96%
“…[37] Introduction of at rimethylsilyl (TMS) group,w hich can be attached and also removed easily, [38] to the alkyne unit was sufficient to produce enantiopure (R)-3-butin-2-ol (ee > 99 % compared to 60 % ee without TMS). [37] In our previous studies [40] we additionally observed that compared to the desilylat-Scheme3.Preparativescale reaction of RasADH with cofactor recycling for the synthesis of alcohol (R)-6. Figure 2.…”
mentioning
confidence: 99%